2003
DOI: 10.1029/2002rg000113
|View full text |Cite
|
Sign up to set email alerts
|

The second law of thermodynamics and the global climate system: A review of the maximum entropy production principle

Abstract: [1] The long-term mean properties of the global climate system and those of turbulent fluid systems are reviewed from a thermodynamic viewpoint. Two general expressions are derived for a rate of entropy production due to thermal and viscous dissipation (turbulent dissipation) in a fluid system. It is shown with these expressions that maximum entropy production in the Earth s climate system suggested by Paltridge, as well as maximum transport properties of heat or momentum in a turbulent system suggested by Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
408
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 369 publications
(421 citation statements)
references
References 114 publications
11
408
1
1
Order By: Relevance
“…Under steady-state flow conditions, the average heat flow rate is closely related to entropy production in the Earth-atmosphere system, as shown by Paltridge [1978] and Ozawa et al [2003] and the MEP corresponds to the maximum convective heat transport [Paltridge, 1978]. The latter was further confirmed by Clausse et al [2012] who showed that the temperature distributions on the Earth surface is consistent with a principle (derived from the constructal law) that convective heat flow rate from equator region to the pole region is maximized, or the resistance to heat flow is minimized at a global scale.…”
Section: Flow Processes In a River Basin And The Earth-climate Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…Under steady-state flow conditions, the average heat flow rate is closely related to entropy production in the Earth-atmosphere system, as shown by Paltridge [1978] and Ozawa et al [2003] and the MEP corresponds to the maximum convective heat transport [Paltridge, 1978]. The latter was further confirmed by Clausse et al [2012] who showed that the temperature distributions on the Earth surface is consistent with a principle (derived from the constructal law) that convective heat flow rate from equator region to the pole region is maximized, or the resistance to heat flow is minimized at a global scale.…”
Section: Flow Processes In a River Basin And The Earth-climate Systemmentioning
confidence: 99%
“…The Earth receives radiation from the hot Sun and transfers the received heat into space. The atmosphere and oceans act as a fluid system that transports heat from the hot region to the cold one with general circulation [Ozawa et al, 2003], because the convection process is more efficient in transferring heat than the conduction process [Bejan, 2000]. Obviously, in this system, the "flow process imposed by its environment" is the heat flow; the heat flow process is the initiator for other flow processes.…”
Section: Flow Processes In a River Basin And The Earth-climate Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…What Lorenz (1960), Paltridge (1975Paltridge ( , 1978Paltridge ( , 2001) and others (see e.g., review by Ozawa et al 2003) showed with more detailed energy balance model simulations is that several observed features of the climate system, such as the intensity of the atmospheric circulation, the equator-pole temperature difference in surface temperature, and the meridional distribution of cloud cover reflect a state of the climate system which is close to a state of MEP.…”
Section: Heat Transport and Maximum Entropy Productionmentioning
confidence: 99%